Free logic : selected essays - Lambert, Karel, 1928- (Cambridge University Press, 2003)
Free logic is an important field of philosophical logic that first appeared in the 1950s. The author was one of its founders and coined the term itself. This collection explores the philosophical foundations of free logic and its application to areas such as the philosophy of religion and computer science.